Soluble biomarkers of HIV-1-related systemic immune activation are associated with high plasma levels of growth factors implicated in the pathogenesis of Kaposi sarcoma in adults - Nana, Benderli Christine; Esemu, Livo Forgu; Besong, Michael Ebangha; Atchombat, Derrick Hyacinthe Nyasse; Ogai, Kazuhiro; Sobgui, Thérèse M. Patricia; Nana, Chris Marco Mbianda; Seumko’o, Reine Medouen Ndeumou; Awanakan, Honoré; Ekali, Gabriel Loni; Leke, Rose Gana Fomban; Okamoto, Shigefumi; et al. (Frontiers in Immunology, 2023)
Background: Human Herpesvirus-8 (HHV-8) is the etiologic agent of Kaposi's sarcoma (KS), a multicentric angio-proliferative cancer commonly associated with Human Immunodeficiency Virus (HIV) infection. KS pathogenesis is a multifactorial condition hinged on immune dysfunction yet the mechanisms underlying the risk of developing KS in HHV-8 seropositive adults remains unclear. Here we explored whether soluble markers of HIV-1-related systemic immune activation (SIA) and angiogenesis (VEGF and FGF acidic) are involved in the pathogenesis of KS in adults with HHV8.Methodology: Blood samples from 99 HIV-1 infected and 60 HIV-1 uninfected adults were collected in Yaoundé, Cameroon. CD3+/CD4+ T cell counts and HIV-1 plasma viral load were determined using the Pima Analyzer and the RT-PCR technique, respectively. Plasma levels of SIA biomarkers (sCD163, sCD25/IL-2Rα, and sCD40/TNFRSF5) and biomarkers of progression to KS (VEGF and FGF acidic) were measured using the Luminex assay. Seropositivity (IgG) for HHV-8 was determined using the ELISA method.Results: Overall, 20.2% (20/99) of HIV-1 infected and 20% (12/60) of HIV-1 uninfected participants were seropositive for HHV8. Levels of sCD163, sCD25/IL-2Rα, sCD40/TNFRSF5, and FGF acidic were higher in the HIV-1 and HHV8 co-infection groups compared to the HIV-1 and HHV8 uninfected groups (all P <0.05). In addition, Higher plasma levels of VEGF correlated with sCD163 (rs = 0.58, P =0.0067) and sCD40/TNFRSF5 (rs = 0.59, P = 0.0064), while FGF acidic levels correlated with sCD40/TNFRSF5 (rs = 0.51, P = 0.022) in co-infected. In HIV-1 mono-infected donors, VEGF and FGF acidic levels correlated with sCD163 (rs =0.25, P = 0.03 and rs = 0.30, P = 0.006 respectively), sCD25/ IL-2Rα (rs = 0.5, P <0.0001 and rs = 0.55, P <0.0001 respectively) and sCD40/TNFRSF5 (rs = 0.7, P <0.0001 and rs = 0.59, P <0.0001 respectively) and even in patients that were virally suppressed sCD25/ IL-2Rα (rs=0.39, P=0.012 and rs=0.53, P=0.0004 respectively) and sCD40/TNFRSF5 (rs =0.81, P <0.0001 and rs=0.44, P=0.0045 respectively).Our findings suggest that although the development of KS in PLWH is multifactorial, HIV-associated SIA might be among the key drivers in coinfections with HHV8 and is independent of the patients' viremic status.